TRADEMARK RIGHTS AS CREDIT COLLATERAL TO STRENGTHEN THE SELF-RELIANCE OF MSMES - Usanti, Trisadini Prasastinah; Sujatmiko, Agung; Kurniawan, Ari (Srawung: Journal of Social Sciences and Humanities, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, and contribute significantly to Gross Domestic Product (GDP) and employment. However, MSMEs often struggle to access adequate financing to support the growth and sustainability of their businesses. One of the main issues is the limited assets that can be used as collateral to obtain credit. The objective of this research is to analyze the availability of trademark rights as credit collateral which can be a solution for MSME businesses that have difficulties in obtaining access to bank funding due to the inability to provide property collateral. This research is a normative research that uses a statutory and conceptual approach. The primary legal materials analyzed are the Trademark and Geographical Indications Law, the Law on Financial Sector Development and Strengthening (PPSK Law), the Copyright Law, the Patent Law and their respective supporting regulations. The result of this research is that the trademark rights of MSME businesses that have been registered at the Directorate General of Intellectual Property and issued a trademark certificate, in addition to obtaining legal protection, can also be used as collateral for bank loans so as to obtain funding from banks, where such funding can help increase the independence of MSME businesses.